Analisis Hukum Kedudukan Keterangan Saksi Anak Terhadap Pembuktian Dalam Penyelesaian Perkara Pidana Di Persidangan - Adella Fajria; Erdianto '; Ferawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
In the trial, there is some flow or process to be undertaken by one was the stage of proof, the proof holds determines to declare one's mistake so it can be a criminal sentenced by the judge. Think the children who became a witness in proving criminal acts cannot provide information under oath, while the CODE of CRIMINAL PROCEDURE requires that any witnesses for sworn in, it would certainly be a matter for the judge's ruling against a drop in criminal cases, especially against criminal cases in which the child becomes the only witness who hear, see and experience itself a criminal offence. As for the writing of theses goals, namely: first, an analysis of the legal position of the child witnesses against proofs in the settlement of criminal cases in court. Second, the basic consideration of judges in meting out the verdict against criminal cases related to the description given by children in court.This type of research can be classified in types of juridical normative research, because in this study the authors use the study material libraries such as official documents, books for research, in this study, the data source used, the primary data, secondary data and data tertier a data-collecting technique in this study with the method of the study of librarianship or documentary studies.From the results of this research can be concluded first, the information of the child cannot be given under oath, is not a legitimate instrument of evidence, but can be used as additional evidence of clue other lawful, for having a rapprochement with valid evidence, the child's information can be the Foundation to strengthen the belief of the judge. Second, information from child witnesses without oath used as instructions based on the rapprochement with other evidence into consideration judges in meting out criminal happens the difference interpretation among the judges in determining the strength of the pembuktiannya to determine the person found guilty or not guilty, judges generally freed terdakwanya with the assessment that the minors who provide information without being sworn in could not be assessed and considered as valid evidence.The author's suggestion, first, a Judge is expected to prosecute criminal cases, especially in the examination and assessment of witnesses against minors should be wise and discerning in looking for material truth of a criminal matter for the sake of a verdict based on real justice. Both need the internal regulation governing judiciary explicitly how should judges consider the child witnesses, as well as through a Supreme Court decision in favor of increasing the power of proof of child witnesses in order that its goals are achieved, namely justice, legal certainty and benefit.Keywords : Law Analysis – Position – Proof – Child Witness